Plant signaling mediates interactions between fall and southern armyworms (Lepidoptera: Noctuidae) and their shared parasitoid cotesia icipe (Hymenoptera: Braconidae) - Tepa-Yotto, G.; Kpongbe, H.; Winsou, J.K.; Agossadou, A.H.; Tamò, Manuele (MDPI, 2025)
In Africa, the current harmful maize pest is Spodoptera frugiperda. Its attack can be severe and cause total economic losses. Spodoptera eridania is another species of the same genus, detected a few months after S. frugiperda’s outbreaks in West and Central Africa. Though both species share a range of host plants, socioeconomic studies are yet to provide specific figures on the potential impacts of S. eridania. The high and inappropriate application of insecticides to control Spodoptera species has negative effects on the environmental elements’ health. Semiochemical tools are increasingly exploited to design alternative pest management strategies. We hypothesize that host plants release components used by the pests and a shared parasitoid to locate the host. To verify that hypothesis, we conducted behavioral assays and GC-MS analyses to identify the potential chemical signals involved in the communications of the moths and their shared parasitoid C. icipe. The results showed that healthy and herbivory-induced maize and amaranth produced some chemical compounds including α-pinene, limonene, isopentyl acetate, (Z)-beta-farnesene, and methyl dodecanoate, which prospects their potential use in alternative pest management strategies for recruiting C. icipe to control these pests. Further work will focus on field validation to develop an alternative control strategy for the moths.